PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SKINTIFIC MOISTURIZER DI PLATFORM TOKOPEDIA - Muhammad Rasyid, Rafi; Rachmansyah, Arief (Jurnal Daya Saing, 2026)
ABSTRACT This research explores the impact of price and product quality on the acquisition of Skintific Moisturizer through the Tokopedia marketplace. Employing a quantitative framework with verificative and descriptive designs, the study gathered primary data via Likert-scaled instruments from a purposive sample of 100 verified customers. The analysis, executed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS, reveals that both variables contribute positively and significantly to buying choices. Notably, the data suggests that pricing strategies exert a more substantial influence than product attributes in shaping consumer final decisions Keywords: Product Quality, Price, Purchase Decision, Skincare, Tokopedia.